Estudio de prefactibilidad y diseño estructural del nuevo Hospital Dr. Pomerio Cabrera de la parroquia de Puerto Bolívar de la ciudad de Machala, provincia de El Oro. - Loayza Loayza, Lady Lissett (2015)
A hospital is essential to atlanta disease epidemics that have lately emerged so strongly to the point that many countries have not even been able to control it, and root cause of this is the lack of adequate special infraestructura under these circumstances . Objective is the structural analysis for a new multifunctional hospital in the parish of Puerto Bolívar , as this is a factor of Zone Z = 0.40 , which gives the caracterizacion high seismic hazard. why it is essential to carry out the preliminary study , the pre design, load analysis , computational modeling , design elements, the study of soils and the budget, which will allow to obtain the structural design of the project .